Polychaete assemblages as indicators of habitat recovery in a temperate estuary under eutrophication - Cardoso, P. G. (2007)
From 1980 to 2000, the Mondego estuary (Portugal) suffered dramatic changes due to eutrophication, leading to a decline in seagrass beds and changes in community structure, namely a decline in species richness and replacement of herbivores by detritivores. Because the conservation status of the estuary was being compromised, a restoration project was implemented in 1998 in order to restore the original natural seagrass habitat. This project included several restoration/management measures, including the protection of the remaining seagrass patches and improvement of the hydraulic conditions through modifying sluice opening regimes, thereby reducing the nutrient loading in the southern arm of the estuary. In addition, several stakeholder forums were convened to inform local people of the ecological and economic importance of the area. In this paper we evaluate the success of this management plan as judged by changes in the polychaete assemblages.